Women as Agents of Change: Female Incomes and Household Decisions in South India - Nancy Luke and Kaivan Munshi (BREAD Policy Paper No. 007, 2004)
This paper exploits a unique setting - tea estates in the South Indian High Range - to provide empirical support for the view that sustained economic empowerment can lead to social and economic change in even the the most disadvantaged sections of society. Female workers earn substantially more than male workers on the tea estates, and these unusual gender patterns have been in place for multiple generations. In addition, low caste and high caste workers have the same incomes and access to the same facilities on the estates. We find that the low castes have higher schooling and are less likely to marry in the traditional fashion than the high castes, reversing the usual pattern that is found in the rest of South India. Our explanation for these striking results is based on the idea that children's schooling and marriage are part of a complex set of inter-linked choices that the household must make in a traditional network-based economy. Although low castes have the same income as the high castes on the tea estates, they have inferior extended family networks at home in Tamil Nadu. They will consequently shift resources away from the home network to the nuclear family, which explains the caste-gap in the schooling and marriage choices that the workers make for their children. Looking within the household to better understand the determinants of these choices, we find that a relative increase in female income increases children's schooling and moves the family away from the traditional social patterns, most significantly among the low castes. Low caste women emerge as independent agents of change, shifting their households from the traditional economy into the modern market economy.